PENGARUH KOMPETENSI PEDAGOGIK, KOMPETENSI PROFESIONAL, KOMPETENSI KEPRIBADIAN DAN KOMPETENSI SOSIAL TERHADAP KINERJA GURU MA DARUSSALAM KATIMOHO KEDAMEAN GRESIK - M. Hasan Mu’arif (Prodi Magister Manajemen Universitas Wijaya Putra, 2023)
This study aims to determine and analyze the effect of pedagogic competence, professional competence, personal competence and social competence on the performance of MA Darussalam Katimoho Kedamean Gresik teachers. A quantitative approach was used in this study with a population of 31 people. The entire population is used as a research sample, hereinafter referred to as the respondent. The results showed that pedagogic competence had a significant effect on teacher performance in MA Darussalam Katimoho Kedamean Gresik, professional had a significant effect on teacher performance in MA Darussalam Katimoho Kedamean Gresik, personality competence had a significant effect on teacher performance in MA Darussalam Katimoho Kedamean Gresik, pedagogic competence had a significant effect on teacher performance in MA Darussalam Katimoho Kedamean Gresik. Pedagogic competence, professional competence, personal competence and social competence simultaneously have a significant effect on the performance of MA Darussalam Katimoho Kedamean Gresik teachers.